Endoplasmic reticulum stress promoted acinar cell necroptosis in acute pancreatitis through cathepsinB-mediated AP-1 activation - Han, Xiao; Li, Bin; Bao, Jingpiao; Wu, Zengkai; Chen, Congying; Ni, Jianbo; Shen, Jie; Song, Pengli; Peng, Qi; Wan, Rong; Wang, Xingpeng; Wu, Jianghong; et al. (Frontiers in Immunology, 2022)
Acinar cell death and inflammatory response are two important events which determine the severity of acute pancreatitis (AP). Endoplasmic reticulum (ER) stress and necroptosis involves in this process, but the relationships between them remain unknown. Here, we analyzed the interaction between ER stress and necroptosis and the underlying mechanisms during AP. Experimental pancreatitis was induced in Balb/C mice by caerulein (Cae) and lipopolysaccharide (LPS) or L-arginine (L-Arg) in vivo, and in pancreatic acinar cells by cholecystokinin (CCK) stimulation in vitro. AP severity was assessed by serum amylase, lipase levels and histological examination. Changes in ER stress, trypsinogen activation and necroptosis levels were analyzed by western blotting, enzyme-linked immunosorbent assay (ELISA), adenosine triphosphate (ATP) analysis or lactate dehydrogenase (LDH) assay. The protein kinase C (PKC)α -mitogen-activated protein kinase (MAPK) -cJun pathway and cathepsin B (CTSB) activation were evaluated by western blotting. Activating protein 1 (AP-1) binding activity was detected by electrophoretic mobility shift assay (EMSA). We found that ER stress is initiated before necroptosis in CCK-stimulated acinar cells in vitro. Inhibition of ER stress by 4-phenylbutyrate (4-PBA) can significantly alleviate AP severity both in two AP models in vivo. 4-PBA markedly inhibited ER stress and necroptosis of pancreatic acinar cells both in vitro and in vivo. Mechanistically, we found that 4-PBA significantly reduced CTSB maturation and PKCα-JNK-cJun pathway -mediated AP-1 activation during AP. Besides, CTSB inhibitor CA074Me markedly blocked PKCα-JNK-cJun pathway -mediated AP-1 activation and necroptosis in AP. However, pharmacologic inhibition of trypsin activity with benzamidine hydrochloride had no effect on PKCα-JNK-cJun pathway and necroptosis in CCK-stimulated pancreatic acinar cells. Furthermore, SR11302, the inhibitor of AP-1, significantly lowered tumor necrosis factor (TNF) α levels, and its subsequent receptor interacting protein kinases (RIP)3 and phosphorylated mixed lineagekinase domain-like (pMLKL) levels, ATP depletion and LDH release rate in CCK-stimulated pancreatic acinar cells. To sum up, all the results indicated that during AP, ER stress promoted pancreatic acinar cell necroptosis through CTSB maturation, thus induced AP-1 activation and TNFα secretion via PKCα-JNK-cJun pathway, not related with trypsin activity. These findings provided potential therapeutic target and treatment strategies for AP or other cell death-related diseases.